2021
DOI: 10.1088/2053-1583/abdf2f
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring and hydrodynamic scaling of shear exfoliated graphene

Abstract: Shear-assisted liquid exfoliation is a primary candidate for producing defect-free two-dimensional (2D) materials. A range of approaches that delaminate nanosheets from layered precursors in solution have emerged in recent years. Diverse hydrodynamic conditions exist across these methods, and combined with low-throughput, high-cost characterization techniques, strongly contribute to the wide variability in performance and material quality. Nanosheet concentration and production rate are usually correlated agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
(75 reference statements)
0
23
0
Order By: Relevance
“…One recent example used real‐time in situ optical microscopy and high‐speed cameras with image processing scripts to track the graphite precursor and the exfoliated sheets to study the speed, agglomeration, and live production rates during shear exfoliation. [ 91 ] The production of few‐layer graphene mechanistically depends on local strain rate distribution and graphite residence time, providing critical exfoliation criteria for scaling. High‐resolution 3D flow simulations were also carried out to further study how strain rate and topology impact exfoliation.…”
Section: Large‐scale Graphene Synthesismentioning
confidence: 99%
“…One recent example used real‐time in situ optical microscopy and high‐speed cameras with image processing scripts to track the graphite precursor and the exfoliated sheets to study the speed, agglomeration, and live production rates during shear exfoliation. [ 91 ] The production of few‐layer graphene mechanistically depends on local strain rate distribution and graphite residence time, providing critical exfoliation criteria for scaling. High‐resolution 3D flow simulations were also carried out to further study how strain rate and topology impact exfoliation.…”
Section: Large‐scale Graphene Synthesismentioning
confidence: 99%
“…Mechanical methods that rely predominantly on shear-driven exfoliation are beneficial as they typically produce defect-free 2D materials without oxidation. Sonication [5], high-shear mixing [6], microfluidisation [7], Taylor-Couette and thin film reactors [8,9] are a few of many examples that have been used successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments by Paton et al [6] and Biccai et al [12] showed there is a minimum shear rate required to overcome van der Waals attractive forces and exfoliate layered materials. Stafford et al [8] recently uncovered the general scaling relationship governing production for continuous flow, shear exfoliation systems. Combining high fidelity numerical simulations (DNS, LES), fluid dynamic experiments and nanomaterial characterisation, it was found that graphene concentration depends on derived parameters of shear rate and particle residence time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations